Utilization of Digital Media in Enhancing the Effectiveness of Da'wah: A Case Study of the Muhammadiyah Da'wah Institution in South Sulawesi - Mahmuddin Mahmuddin; Alamsyah Alamsyah (Eduvest - Journal of Universal Studies, 2026)
This research is focused on the main subject, namely how to use digital media in increasing the effectiveness of da'wah: A case study of the Da'wah Institute of the Muhammadiyah Regional Executive of South Sulawesi, The formulation of the research problem is: what is the form of the use of digital media carried out by the Da'wah Institute of the Muhammadiyah Regional Executive of South Sulawesi? What is the impact of the use of digital media on the reach and effectiveness of da'wah messages by the da'wah institution of the Muhammadiyah Regional Executive of South Sulawesi? What is the response and involvement of the younger generation to the da'wah content delivered through digital media by the Da'wah Institute of the Muhammadiyah Regional Executive of South Sulawesi? This study used a qualitative descriptive approach with a case study method on the Muhammadiyah Da'wah Institute of South Sulawesi which has introduced digital da'wah as a tool for spreading da'wah. Primary data is collected by researchers directly from the original source. Meanwhile, secondary data is obtained from existing sources such as books from magazines and other sources. The results of the study show that the South Sulawesi Muhammadiyah da'wah institution actively utilizes various digital platforms such as YouTube, Instagram, TikTok, and podcasts as a means of disseminating creative and contextual religious messages. The use of digital media has been proven to significantly increase the reach of the audience, especially among urban and younger generations.